L’observatoire de Juvisy-sur-Orge, l’« univers d’un chercheur » à sauvegarder - Colette Aymard; Laurence-Anne Mayeur (In Situ)
In 1882, Camille Flammarion was given a property at Juvisy-sur-Orge by one of his admirers. He transformed the house into an astronomical observatory and installed what was for its day advanced scientific equipment. A large number of objects still survive there, bearing witness to astronomy and to its progress during the nineteenth century, and also to the careeer of a scientific figure. Today, apart from its dome, the building is in a poor state of repair and the collections are stored in outbuildings. The building, property of the Société astronomique de France (French Astronomical Society), requires considerable restoration work in order to be able to shelter the collection and bear witness anew to the world of this nineteenth-century researcher.